Effectuation of Pleurotus pulmonarius on hypercholesterolemic wistar-kyoto rats : analysis on liver and sera - Noor Fazila Mohd Yahaya,; Norhaniza Aminudin,; Noorlidah Abdullah, (Universiti Kebangsaan Malaysia, 2022)
Hypercholesterolemia is one of the potential risks of cardiovascular heart disease (CHD). An early diagnosis and treatment attenuate the risk of CHD. Besides statin prescription for hypercholesterolemia, functional food has an added value to ameliorate the risk. This study was conducted to analyse the significant effect of grey oyster mushroom (Pleurotus pulmonarius) on hypercholesterolemia. Thirty-six Wistar-Kyoto rats were assigned into six groups, consisted of normal (N), hypercholesterolemia (H), two groups for prevention (P1 and P2), and two groups for treatment (T1 and T2). For prevention purpose, P1 and P2 were concomitantly induced to be hypercholesterolemic and fed with either crude aqueous extract of P. pulmonarius (CA) or simvastatin for 45 days. Following 45 days of hypercholesterolemic-induction, T1 and T2 rats were then orally fed with either CA or simvastatin for another 30 days. On day 45, groups N, H, P1, and P2 were sacrificed, whereas groups T1 and T2 were sacrificed on day 75. Histopathology examination showed the conditions of liver tissues. Fat droplets were observed in hypercholesterolemic hepatic tissues and were also remained in the hepatic tissues of rats belonged to the treatment groups. The tissues’ viability was better in prevention groups suggesting the compound(s) present in CA might be able to protect them from further damage. Metabolomic analysis of the sera from P1 and T1 rats showed altered regulation of several metabolites such as pantothenic acid, N-carbamylglutamate, serotonin and ceramide against the control group.